Crowd-based collaboration caching mechanism in smart identifier network - Haifeng LI; Wei QUAN; Nan CHENG; Hongke ZHANG; Xuemin SHEN (物联网学报)
Smart identifier network (SINET) is an innovative network architecture.Through dynamic collaboration of service resource,function groups and physical components,the network scalability,resource utilization and service quality were effectively improved by SINET,and an effective solution for the development of industrial Internet of things(IoT) could be provided.To promote content delivery in resource-constrained IoT,caching function was introduced in network components by SINET,and the bandwidth waste caused by traffic redundancy in resource-constrained node could be reduced.Therefore,how to efficiently cache content became an important research topic.Based on SINET architecture,a crowd-based collaboration cache (C2Cache) mechanism was proposed in this scheme.According to the actual network topology,the caching function group was dynamically created and optimized by C2Cache,and a function group as crowd minimum unit to execute the maximum benefit cache (MBC) algorithm was defined to maximize the caching space efficiency.With the self-developed emulation system,named EmuStack,the performance of C2Cache was evaluated.The experimental results show that,comparing with LCE,Random,Prob Cache,LCD and Greedy caching mechanisms,the cache hit rate can be improved effectively,then the average access time can be reduced significantly by C2Cache.In the simulated network scenario,the performance increases 15% to 30%.